2020
DOI: 10.3389/fnut.2020.589737
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COVID-19 Lockdown Restrictions on Perceived Nutrition Habits in Rugby Union Players

Abstract: The global outbreak of COVID-19 has led to governments and local authorities implementing nationwide lockdowns in an attempt to encourage social distancing and minimize the spread of the virus. Only essential businesses have been able to remain open, with non-essential businesses and activities either closing or restricting services. With no group training sessions allowed, canceled matches, an inability to work and the closure of eating establishments, Rugby Union players have experienced disruption to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 37 publications
3
33
0
7
Order By: Relevance
“…Moreover, a study of professional/semi-professional rugby union players in New Zealand found the majority of players to have a reduced intake of packaged/convenience foods and greater fruit and vegetable consumption during the COVID-19 pandemic. Findings were similar to the present study, and players reported lack of motivation and limited access to training equipment as challenges during lockdown (Roberts et al 2020). Concerns over the impact of reduced training and its impact on BC was cited by a few players, which may have detrimental impact on future performance.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, a study of professional/semi-professional rugby union players in New Zealand found the majority of players to have a reduced intake of packaged/convenience foods and greater fruit and vegetable consumption during the COVID-19 pandemic. Findings were similar to the present study, and players reported lack of motivation and limited access to training equipment as challenges during lockdown (Roberts et al 2020). Concerns over the impact of reduced training and its impact on BC was cited by a few players, which may have detrimental impact on future performance.…”
Section: Discussionsupporting
confidence: 89%
“…In these circumstances, athletes have encountered issues not only related to their options to compete and maintain their usual training routines but also challenges presented by social isolation and need to distance from partners and teammates ( Schinke et al, 2020 ). This has resulted in a decrease in athletes’ training intensity and training volume and other consequences such as a reduction of sleep quality ( Mon-López et al, 2020 ) and changes in their dietary patterns ( Roberts et al, 2020 ). Athletes have also reported COVID-19-related psychological distress and worries about one’s sport and about one’s own future in sport ( Håkansson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, athletes’ goal motives (autonomous and controlled) as possible mechanisms by which resilience can predict changes in subjective vitality during the COVID-19 pandemic was examined. A number of recent studies, conducted across different populations and countries, have described the impact of COVID-19 lockdown on athletes (e.g., Håkansson et al, 2020 ; Mon-López et al, 2020 ; Pillay et al, 2020 ; Roberts et al, 2020 ). However, to our knowledge, there has been no research about the role of resilience and goal motives on changes in athlete’s subjective vitality during lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies provided important information about the negative effects of detraining periods on performance parameters [10][11][12][13][14][15][16][17]. For example, Morais et al [19] investigated the effect of an 11-week detraining period on some athletic performance components of swimmers and they found impaired performance.…”
Section: Discussionmentioning
confidence: 99%
“…-Coaches and performance staff should ensure athletes receive appropriate nutritional and training support whilst being aware of the unique demands the individuals may face [12].…”
mentioning
confidence: 99%